CE: The Use of Resuscitative Endovascular Balloon Occlusion of the Aorta in Treating Hemorrhagic Shock from Severe Trauma. Issue 10 (October 2018) - Cheema, Fareed; Garcia, Carrie; Rivera, Aksim G.; Chao, Edward
Abstract : N/A: Hemorrhage is the leading cause of preventable death in trauma patients. In recent years, technological innovations and research efforts aimed at preventing death from hemorrhagic shock have resulted in the emergence of resuscitative endovascular balloon occlusion of the aorta (REBOA). REBOA offers a less invasive option for emergent hemorrhage control in noncompressible areas of the body without the added risks and morbidities of an ED thoracotomy. This article outlines the procedure and device used, describes the procedure's evolution, and discusses various considerations, pitfalls, and nursing implications. Abstract : Efforts to prevent death from hemorrhagic shock have resulted in the emergence of resuscitative endovascular balloon occlusion of the aorta (REBOA), a less invasive option for controlling hemorrhage in noncompressible areas of the body. This article outlines REBOA, describes its evolution, and discusses various considerations, pitfalls, and nursing implications.